Marketing digital como fator de desenvolvimento do empreendedorismo feminino na cidade de Parintins/AM - Oliveira, David Fonseca de (Brasil, 2023)
This article addresses the contributions of digital marketing to the growth of female entrepreneurship. Due to the constant changes in the job market, there has been an increase in the participation of women in the business world. The main objective of this study is to highlight digital marketing as a factor in the development of female entrepreneurship in the city of Parintins/AM. The methodology is based on qualitative research, aiming at a deeper understanding of the phenomenon studied and its meanings. As for the methods of procedure, bibliographic research and field research were defined. The main instrument for data collection was the standardized interview, applied to three women entrepreneurs in the city of Parintins. The theoretical basis presents authors such as: Sampaio & Tavares (2014), Kotler (2010) and Brito (2013). The results show that the insertion of digital marketing in the processes of management, performance, product sales and customer adhesion contributed significantly to the development of female entrepreneurship in the city of Parintins/AM. The entrepreneurs consider that the use of social networks, linked to the daily sharing of content, photos and videos, has brought a return on engagement, profitable return, visibility and customer loyalty.